2018
DOI: 10.1101/325118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Illumina sequencing analysis of the ruminal microbiota in high-yield and low-yield lactating dairy cows

Abstract: 9In this study, differences in the ruminal bacterial community between high-yield and 10 low-yield lactating dairy cows fed the same diets were investigated. Sixteen lactating 11 dairy cows with similar parity were divided into two groups based on their milk yield: 12 high-yield (HY) and low-yield (LY) groups. On day 21, rumen content samples were 13 collected, and the microbiota composition was determined using Illumina MiSeq 14 sequencing of the 16S rRNA gene. During the study period, dry matter intake (D… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The development of high-throughput sequencing technology has enabled advancements in the understanding of the gastrointestinal microbiota of ruminant animals in recent years. Studies on the microbiota present in rumen during lactation have found that the ruminal microbial structure and composition varied with lactation period (Bainbridge et al 2016 ; Lima et al 2015 ; Xue et al 2018 ), and revealed an association between the rumen microbiota and milk efficiency (Weimer et al 2017 ), feed efficiency (Shabat et al 2016 ) and milk production (Indugu et al 2017 ; Tong et al 2018 ) in dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…The development of high-throughput sequencing technology has enabled advancements in the understanding of the gastrointestinal microbiota of ruminant animals in recent years. Studies on the microbiota present in rumen during lactation have found that the ruminal microbial structure and composition varied with lactation period (Bainbridge et al 2016 ; Lima et al 2015 ; Xue et al 2018 ), and revealed an association between the rumen microbiota and milk efficiency (Weimer et al 2017 ), feed efficiency (Shabat et al 2016 ) and milk production (Indugu et al 2017 ; Tong et al 2018 ) in dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has focused on elucidating the effects of endophyte-infected tall fescue on performance and other physiological parameters, but few studies have been conducted to evaluate its effects on the rumen microbiota. It is important to evaluate the effects of these bioactive alkaloids on the rumen and its microbial population, as the microbial population directly aids in providing nutrients to the ruminant host by forage fermentation (i.e., tall fescue) and also impacts lactation energy requirements ( 14 , 15 ). Rumen microorganisms are able to degrade many of the ergot alkaloids consumed by the hosts; however, the identification of the organisms responsible for toxicity degradation is unknown ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Here, Ruminococcus and Eubacterium were numerically higher in farm A and farm B, respectively. The study conducted by Tong et al (2018) showed higher abundances of Ruminococcus 2 and Eubacterium coprostanoligenes in high yield cows. Eubacterium has also been associated with low residual feed intake (Elolimy et al, 2018), and this genus is involved in cellulose degradation in the rumen and some species FIGURE 6 | Heat map of the top 10 ECs selected by how well they distinguish (A) farm, (B) body site, and (C) farm given body site.…”
Section: Microbiomementioning
confidence: 92%
“…Fibrobacter succinogenes (genus Fibrobacter) are butyrate-producing bacteria present in the rumen fluid, and this genus was higher in farm A compared to farm B. Prevotella and Bacteroides were the most abundant genera in almost all samples of this study. Prevotella has been reported to be the most abundant genus in the rumen (Chaucheyras-Durand and Ossa, 2014;Jami et al, 2014;Lima et al, 2015;Tong et al, 2018), whose species are related to degradation of starch, hemicellulose, and protein (Henderson et al, 2015). Prevotella has also been positively correlated with milk production (Lima et al, 2015;Indugu et al, 2017).…”
Section: Microbiomementioning
confidence: 99%